ANALISIS FAKTOR YANG MEMPENGARUHI KELELAHAN PADA PEKERJA DRIVER GRAB KOTA MEDAN - Susilawati Susilawati; Mardiah Batubara (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2024)
Grab is one of the originators of online-based transportation. The presence of Grab helps people with their transportation needs. Grab is the leading ride-hailing platform in Southeast Asia. Work activities carried out by online drivers sometimes do not look at the time, many even work from early morning until late at night to get maximum points and bonuses in one day. The purpose of this study was to analyze the factors that influence fatigue in Grab driver workers in Medan City. This research uses a type of quantitative study, with a cross-sectional research design. The sample in this study were 80 respondents. The data analysis used was univariate, bivariate, and multivariate analysis using the Chi-Square Test. The results of the study found that the relationship between age and fatigue was p-value 0.007 <0.05, the relationship between years of service and fatigue was p-value 0.000 <0.05. Multivariate analysis obtained a significant variable, namely work mass (P Value = 0.006). Work period has a very close relationship to driver grab fatigue in the city of Medan. For online motorcycle taxi drivers to be aware of the importance of resting if they are tired to avoid work fatigue.